Effects of Astrocaryum aculeatum Meyer (Tucumã) on Diet-Induced Dyslipidemic Rats - Geórgia Craveiro Holanda Malveira Maia; Mozer da Silva Campos; Janice Barros-Monteiro; Juan Eduardo Lucas Castillo; Murilo Soares Faleiros; Rejane Souza de Aquino Sales; Denise Moraes Lopes Galeno; Edson Lira; Francisca das Chagas do Amaral Souza; Carmen Ortiz; Luisa Morales; Rosany Piccolotto Carvalho (Journal of Nutrition and Metabolism)
An in vivo study was conducted to assess the effects of the consumption of Astrocaryum aculeatum Amazon Meyer (tucumã) in the treatment of diet-induced dyslipidemia in sedentary and exercised Wistar rats. With an average weight of 350 grams, 40 male rats were divided into 4 subgroups of 10. The sedentary control group (SCG) was fed with commercial feed, while the sedentary treatment group (STG) was fed with a ration of tucumã. In addition to the sedentary groups, two exercise groups were formed. The Exercised control group (ECG) was fed with commercial food and the exercised treatment group (ETG) was fed with a ration of tucumã. Body weight gain and food intake were monitored during the experiment. Plasma was analyzed for cholesterol, triglycerides, HDL-C, LDL-C, VLDL, total protein, glucose, insulin, and leptin concentrations. Our results show that the ECG group tended to consume more food, while the groups that were fed with tucumã pulp (STG and ETG) presented a greater tendency to gain body mass. ECG group showed a tendency towards a higher concentration of cholesterol in plasma, while STG and ETG presented higher absolute values for triglycerides and VLDL. No hypolipiemic effect was observed related to tucuma ingestion.